2016
DOI: 10.1002/ana.24746
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomic Correlates of Female Sexual Dysfunction in Multiple Sclerosis

Abstract: Our data indicate that impaired female sexual arousal is associated with MS lesions in the occipital region, integrating visual information and modulating attention toward visual input. Impaired lubrication correlated with lesions in the left insular region, contributing to mapping and generating visceral arousal states. Ann Neurol 2016;80:490-498.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 52 publications
1
40
0
2
Order By: Relevance
“…In female and male MS patients, Zivadinov et al [16] and Zorzon et al [17] found associations between SD and pontine lesions. Our group recently showed associations between the site of MS-specific cerebral lesions and female SD [14,15]. We found associations between right occipital lesions and impaired arousal and between left insular lesions and decreased lubrication [14].…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…In female and male MS patients, Zivadinov et al [16] and Zorzon et al [17] found associations between SD and pontine lesions. Our group recently showed associations between the site of MS-specific cerebral lesions and female SD [14,15]. We found associations between right occipital lesions and impaired arousal and between left insular lesions and decreased lubrication [14].…”
Section: Discussionsupporting
confidence: 53%
“…Our group recently showed associations between the site of MS-specific cerebral lesions and female SD [14,15]. We found associations between right occipital lesions and impaired arousal and between left insular lesions and decreased lubrication [14]. In another study, we found that MS lesions in left temporal periventricular and right visual association areas compromise orgasmic function [15].…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations